Renal function in PUSH-AHF: a summary of newly released data from the 2024 Annual Congress of the Heart Failure Association of the ESC - Yacob, Alexander Aaron; Flint, Kelsey M. (Heart failure reviews, 2024)
The Pragmatic Urinary Sodium-based algoritHm in Acute Heart Failure (PUSH-AHF) study, published in August of 2023, was the first randomized clinical trial to compare natriuresis-guided decongestion (based on spot urinary sodium measurement) to standard of care in patients with acute heart failure with congestion receiving loop diuretic therapy. Based on results from their trial, the authors concluded that natriuresis-guided loop diuretic treatment was safe and improved natriuresis and diuresis without impacting long-term clinical outcomes. The original PUSH-AHF trial included limited information about renal outcomes and left clinicians with important questions about how natriuresis-guided decongestion might affect their patients’ renal function. On May 12, 2024, however, at the 2024 Annual Congress of the HFA-ESC, Dr. Kevin Damman provided an in-depth exploration of renal outcomes from the trial when he presented a pre-specified, secondary analysis, renal function in the PUSH-AHF trial. This review puts the sub-study findings into context by considering the history of the original trial from which they came from and explaining the need for a close study of its renal outcomes particularly. It highlights the potential impact of renal function in PUSH-AHF on clinical practice and future directions that should be considered by the cardiology research community.